Team Member Functional Background and Involvement in Management Teams: Direct Effects and the Moderating Role of Power Centralization - Bunderson, J. Stuart (Academy of Management Journal, 2003)
This article examines the relationship between a team member's functional background and two forms of intrateam involvement: centrality in a team's workflow and involvement in team decision making. It is argued that a functional background that provides valued expertise and one that is similar to the functional backgrounds of other team members will be associated with both forms of involvement; however, power centralization in a team will be a critical moderator of the decision involvement relationship. Tests of these hypotheses in a sample of business unit management teams provided strong support.